2017
DOI: 10.1002/hep.29486
|View full text |Cite
|
Sign up to set email alerts
|

Therapies for advanced stage hepatocellular carcinoma with macrovascular invasion or metastatic disease: A systematic review and meta‐analysis

Abstract: Hepatocellular carcinoma (HCC) is a complex disease most commonly arising in the background of chronic liver disease. In the past two decades, there has been a significant increase in our understanding of both the clinical and molecular heterogeneity of HCC. There has been a robust increase in clinical trial activity in patients with poor prognostic factors, such as macrovascular invasion and extrahepatic spread (EHS). We aimed to synthesize the evidence for the treatment of patients with advanced HCC based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
145
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(146 citation statements)
references
References 26 publications
1
145
0
Order By: Relevance
“…Over the past 10 years, sorafenib remains the most widely systemic drug for advanced HCC . However, the response to sorafenib seems to be moderate, as shown in the SHARP and AP trials .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 10 years, sorafenib remains the most widely systemic drug for advanced HCC . However, the response to sorafenib seems to be moderate, as shown in the SHARP and AP trials .…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide and is the second‐leading cause of cancer death globally, with increasing incidence and mortality rates . Sorafenib is the most recommended first‐line systemic therapy for advanced HCC worldwide . However, its therapeutic efficacy in HCC is far from satisfactory .…”
mentioning
confidence: 99%
“…Presently, sorafenib and bevacizumab are the most widely used targeted therapies in liver cancer treatment [14,15]. Sorafenib, a multikinase inhibitor that blocks the activation of kinases associated with the regulation of tumor growth and angiogenesis, has been recognized as the most effective targeted drug against liver cancer [16]; however, it only prolongs patient survival by approximately 3 months [17,18]. Additionally, most drugs that target liver cancer can cause severe side effects that inevitably have a profound negative impact on the patient's quality of life [19].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed that vascular invasion is an independent risk factor for the prognosis of HCC patients who underwent surgical treatment [22][23][24]. The presence of vascular invasion of the portal or hepatic veins is associated with a high risk of tumour recurrence and is regarded as a prerequisite for systemic tumour dissemination [25,26]. Our study revealed that TRIM4 expression levels in HCC tissues were negatively associated with vascular invasion and the absence of a tumour capsule, indicating that TRIM4 may be a potential prognostic marker for HCC.…”
Section: Discussionmentioning
confidence: 99%